2016
DOI: 10.3390/ijms17081344
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Antioxidant Activity of Crude Extract and Polyphenolic Rich Fractions from C. incanus Leaves

Abstract: Cistus incanus (Cistaceae) is a Mediterranean evergreen shrub. Cistus incanus herbal teas have been used as a general remedy in traditional medicine since ancient times. Recent studies on the antioxidant properties of its aqueous extracts have indicated polyphenols to be the most active compounds. However, a whole chemical characterisation of polyphenolic compounds in leaves of Cistus incanus (C. incanus) is still lacking. Moreover, limited data is available on the contribution of different polyphenolic compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 53 publications
(70 reference statements)
8
37
0
Order By: Relevance
“…Having read several scientific publications on Cistus spp. and comparing them with the herein presented results it can be clearly seen, that similar components of phenolic nature are identified and listed by different authors [7,12].…”
Section: Qualitative and Quantitative Analyses Of C Incanus And C Lsupporting
confidence: 72%
See 2 more Smart Citations
“…Having read several scientific publications on Cistus spp. and comparing them with the herein presented results it can be clearly seen, that similar components of phenolic nature are identified and listed by different authors [7,12].…”
Section: Qualitative and Quantitative Analyses Of C Incanus And C Lsupporting
confidence: 72%
“…The highest antioxidant activity was shown for 60% SOX (IC 50 = 3.81 ± 0.36 µg/mL) and 60% M C. incanus extract (IC 50 = 4.05 ± 0.43 µg/mL) ( Table 2). Previous studies showed that C. incanus extracts and polyphenolic rich fractions are effective DPPH scavengers (IC 50 = 2.99 ± 1.18 µM for crude ethanolic extract and 0.92 ± 0.10 µM for ethyl acetate fraction in DPPH scavenging assay) [12]. The antioxidant activity of polyphenols from C. incanus was also confirmed by in vitro studies, where incubation of hamster fibroblast cells (V79) with C. incanus fraction enriched in catechins and procyanidins reduced the intracellular ROS levels by 30-40% [28].…”
Section: Content Of Total Phenolics Flavonoids and Antioxidant Actimentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention was devoted to the evaluation of radical scavenging activity, via Trolox‐equivalent antioxidant capacity assays (TEAC) following the quenching of two different radicals, ABTS cation, through UV‐Vis spectrophotometry, and neutral DPPH, through UV‐Vis and EPR techniques (Polovka, ; Prior, Wu, & Schaich, ; Thaipong, Boonprakob, Crosby, Cisneros‐Zevallos, & Byrne, ; Yu & Cheng, ). EPR spectroscopy is a straightforward tool for the radical determination, and it has been previously applied for the determination of antioxidant activity of crude extracts and galloyl quinic derivatives, as well as antioxidant defense and oxidative damage processes evaluation against stress conditions (Baratto et al, ; Fini et al, ; Gori et al, ; Megar et al, ). Selected polyphenols have been also identified and quantified through HPLC‐UV and HPLC‐MS/MS techniques, optimizing the analytical protocols on the basis of the chemical properties of the matrix and analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Cistaceae is a small family of plants comprising shrubs that are commonly found in the Mediterranean climate [1,2]. The plants of Cistus species are used in the preparation of folk medicines, in the form of anti-diarrheal agents, to provide protection against various skin diseases, and as anti-inflammatory agents [2,3]. Different species of Cistus are used as herbal infusions, food additives, or nutraceutical products [4].…”
Section: Introductionmentioning
confidence: 99%